Effect of Imidacloprid and Chloropyrifos Toxicity on Earthworm Amynthas alexandri Under Laboratory Conditions - Miglani, Rashi; Parveen, Nagma; Rawat, Gaurav; Sharma, Netrapal; Kumar, Ankit; Bisht, Satpal Singh (Asian Journal of Biological and Life Sciences)
Aim: To highlight the impact of commonly used insecticides on earthworms as they represent the largest fraction of soil biomass. Earthworms were exposed to different concentrations of insecticides using a contact filter paper test method. Materials and Methods: Acute toxicity was tested for 48 hr using a filter paper contact toxicity test (Whatman filter paper no.1). After 48 hexposure, morphological changes and DNA Damage were observed and the treated earthworms were fixed with 10% (w/v) for 24 h in formalin solution for the histological test. Results: Based on Median lethal concentration, the insecticides applied at the field recommended dose in the study are classified as super toxic in the contact filter toxicity test. The highest mortality was caused by Imidacloprid and found to be the most toxic. Conclusion: Insecticides even when used at field recommended doses cause lethal effects on various activities of earthworms including DNA damage and reduced reproductive potential leading to a poor density of earthworms including poor soil fertility. The altered morphological and histological changes were also observed when earthworms get direct or indirect exposure to insecticides. Therefore, it is important to standardize and rationalize the use of pesticides simultaneously a higher degree of awareness and education as needed at all levels including the vendors and producers of pesticides.
Keywords: Amynthas alexandri.; Chloropyrifos; Imidacloprid; LC50; Toxicity